The Effect of Different Plasma Treatments on the Surface Properties and Bond Strength between Lithium Disilicate and Resin Cement - Bitencourt, Sandro Basso [UNESP]; Piacenza, Lucas Tavares [UNESP]; Souza, João Paulo do Vale [UNESP]; Silva, Emily Vivianne Freitas da [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Barão, Valentim Adelino Ricardo; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP] (My University, 2020)
Purpose: To evaluate the roughness, surface energy, and the bond strength of lithium disilicate yielded by two different types of nonthermal plasma (NTP), oxygen- or argon-based, compared to the conventional method. Materials and Methods: Ninety-three lithium disilicate (IPS e.max Press) samples were divided into 3 groups: HF (hydrofluoric acid group); ONTP (oxygen-based NTP group); ANTP (argon-based NTP group). Surface energy and roughness analyses were performed before and after surface treatment, and bond strength testing was performed before and after 5000 thermocycles. Scanning electron microscopy (SEM) was used to characterize the surface treatments. Data were submitted to ANOVA and Bonferroni's test with statistical significance set at 5%. Results: The ONTP group presented the highest surface energy values, followed by ANTP and HF. In addition, the ONTP group had higher surface roughness. SEM revealed exposed lithium disilicate crystals in the HF group, but a homogeneous film coverage in both NTP groups. Regarding bond strength, ANTP presented statistically significantly higher values than the other groups before thermocycling, and statistically significantly lower values than the other groups after thermocycling. The HF and ONTP groups presented statistically similar values after thermocycling. Conclusion: The bond strength of resin cement to lithium disilicate obtained after oxygen-based NTP was comparable with that obtained after conventional hydrofluoric acid treatment.
Keywords: ceramic; lithium disilicate; nonthermal plasma; shear bond strength; surface treatment